2018
DOI: 10.1371/journal.pntd.0006663
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma haematobium effects on Plasmodium falciparum infection modified by soil-transmitted helminths in school-age children living in rural areas of Gabon

Abstract: BackgroundMalaria burden remains high in the sub-Saharan region where helminths are prevalent and where children are often infected with both types of parasites. Although the effect of helminths on malaria infection is evident, the impact of these co-infections is not clearly elucidated yet and the scarce findings are conflicting. In this study, we investigated the effect of schistosomiasis, considering soil-transmitted helminths (STH), on prevalence and incidence of Plasmodium falciparum infection.Methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
64
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(75 citation statements)
references
References 47 publications
9
64
2
Order By: Relevance
“…However, they have generated contradictory findings. Lower parasite densities (PD) and a lower incidence of Pf infection or malaria‐related complications in children infected by Sh have been reported, whilst other studies have reported an increased risk of Pf infections or higher PD associated with Sh or S mansoni coinfections . The lack of an association between Schistosoma infection and the risk of Pf infection has also been reported in Kenya, Ethiopia and Uganda .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, they have generated contradictory findings. Lower parasite densities (PD) and a lower incidence of Pf infection or malaria‐related complications in children infected by Sh have been reported, whilst other studies have reported an increased risk of Pf infections or higher PD associated with Sh or S mansoni coinfections . The lack of an association between Schistosoma infection and the risk of Pf infection has also been reported in Kenya, Ethiopia and Uganda .…”
Section: Introductionmentioning
confidence: 99%
“…Lower parasite densities (PD) and a lower incidence of Pf infection or malaria-related complications in children infected by Sh have been reported, [3][4][5][6][7] whilst other studies have reported an increased risk of Pf infections or higher PD associated with Sh or S mansoni coinfections. [8][9][10][11][12] The lack of an association between Schistosoma infection and the risk of Pf infection has also been reported in Kenya, Ethiopia and Uganda. 13,14 Differences in parasite exposure and related anti-parasitic immunity, study population and design, as well as the sensitivity of diagnostic tools could partly explain these discordant observations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil-transmitted helminths infection (Ascaris Lumbricoides, Trichuris trichiura, and Hookworm) alone affects 1.5 billion people worldwide [7]. Sub-Saharan Africa bears the highest-burden for both helminths infection and other intestinal parasitic infections [8].…”
Section: Introductionmentioning
confidence: 99%
“…This study was conducted at the Centre de Recherches Médicales de Lambaréné (CERMEL) located in the semi-rural setting of Lambaréné, Gabon, where UGS is highly prevalent. [14][15][16][17][18][19] It was part of a larger study, which additionally assessed epidemiological aspects as well as immunological and metabolomic aspects of UGS; these will be reported separately. Procedures relevant for the pilot assessment of the POCUS protocol were: (1) development of a POCUS scan protocol; (2) the training of two operators; (3) evaluation of the diagnostic accuracy of POCUS operators, using remote expert image review as a reference; and (4) comparing the ultrasound findings with parasitology test results.…”
Section: Methodsmentioning
confidence: 99%